IMPLEMENTASI METODE SHORTEST-JOB FIRST UNTUK PENJADWALAN PENGGUNAAN LABORATORIUM FISIKA DI SMA 1 PEGAJAHAN (Universitas Methodist Indonesia, 2022)
Queuing problems can occur in many cases, including in the process of using the physics laboratory by patients. the use of the physics laboratory at SMA Negeri 1 Pegajahan experienced problems such as recording the Order Form which was still done manually, this resulted in frequent data accumulation, loss and even miscommunication. This study aims to make a schedule for the use of the physics laboratory to overcome the queue problem. In this study, the author uses the Shortest Job First (SJF) algorithm, which is a scheduling method by determining that each process in the ready queue will be executed based on the smallest burst time so that the waiting time is short for each process and the average waiting time is also short. Based on the existing problems, it can be concluded that there is a need for a physics laboratory scheduling system using the shortest job first method that can manage and determine the usage schedule according to the duration that has been made.